Effect of salicylic acid on carotenoids and chlorophyll content in Mas Cotek (Ficus Deltoidea Jack Var. Trengganuensis) leaves and its Retinol Activity Equivalents (RAE) - ISMAIL, Azrina; Shahidan, Norshazila; Mat, Nashriyah; Othman, Rashidi (SET PUBLISHER, 2020)
This study was conducted to determine the effect of different concentrations of salicylic acid (SA) (control, 0.01, 0.10, 1.00 mM) on carotenoids and chlorophyll content and its retinol activity equivalents (RAE) value in Ficus deltoidea Jack var. trengganuensis leaves. In this study, 12 seedlings of Ficus deltoidea Jack var. trengganuensis were sprayed with different concentrations of SA. Carotenoid content was determined using High-Performance Liquid Chromatography (HPLC) and chlorophyll content was determined using chlorophyll meter. Retinol activity equivalents were calculated using RAE formulation. From the results obtained, two types of carotenoids, lutein and β-carotene, were detected in HPLC. The highest lutein and β-carotene content present in Ficus deltoidea Jack var. trengganuensis leaves extract was found in 0.10 mM SA treatment (93.50b ± 0.71 μg/g DW) for lutein and (282.00b ± 46.67 μg/g DW) for β-carotene, while the lowest lutein compound was found in 1.00 mM SA treatment (30.25a ± 1.77 μg/g DW) while the least β-carotenoid content was found in (1.00 mM SA) treatment (63.00a ± 0.71 μg/g DW). The same goes for retinol activity equivalents, the highest retinol activity equivalents was recorded in 0.10 mM SA treatment while lowest in 1.00 mM SA treatment. For chlorophyll content, the highest reading was showed in 0.10 mM SA treatment (73.50b ± 0.71 μg/g DW) while the lowest reading was in 1.00mM SA treatment (42.10a ± 1.41 μg/g DW). From this study, it can be concluded that salicylic acid at a certain concentration could increase or improve the carotenoid or chlorophyll content. Thus, it could be an alternative source of carotenoid and chlorophyll for the food and pharmaceutical industry in the future.